2013
DOI: 10.1177/1947601913479798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirtuins in Stem Cell Differentiation

Abstract: Sirtuins play an essential role in the cellular response to environmental stress, promoting DNA repair, telomere stability, cell cycle arrest, cellular senescence, and apoptosis. Much attention has been given to the role of sirtuins in aging and cancer development; however, less is known about their role in stem cell regulation. This review focuses in this topic and discusses the possible implications in adult stem cell aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 104 publications
(169 reference statements)
0
29
0
Order By: Relevance
“…Significant alterations of the cellular redox status have been demonstrated during both self-renewal and cell differentiation33. To study whether HX modifies levels of the intracellular nucleotide NAD, we performed nicotinamide assay and demonstrated higher levels of NAD in white matter cells after HX (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significant alterations of the cellular redox status have been demonstrated during both self-renewal and cell differentiation33. To study whether HX modifies levels of the intracellular nucleotide NAD, we performed nicotinamide assay and demonstrated higher levels of NAD in white matter cells after HX (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SIRT1 is plays an important role in cell survival, signal transduction, and apoptosis, by deacetylation of specific cell signaling molecules (p53, FOXO3, FOXO4, NF-kB, and HIFs) [36,37]. However, a few studies have suggested that SIRT1 may act as a tumor activator in various human cancers, including breast cancer, prostate cancer, or ovarian cancer [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Protein acetylation is emerging as an evolutionarily conserved regulatory mechanism involved in coordinating a variety of metabolic pathways in response to different conditions, including glycolysis, fatty acid synthesis, gluconeogenesis, cell cycle, DNA repair, cell survival and differentiation, mitochondrial biogenesis, and autophagy . This is achieved by epigenetic modulation of histone and nonhistone proteins in the nucleus, to regulate gene expression, and by modulation of specific protein substrates within the mitochondria and the cytoplasm .…”
Section: Discussionmentioning
confidence: 99%